Self-monitoring in social networks. (1st January 2012) - Anjomshoaa, Amin; Vo Sao, Khue; Tahamtan, Amirreza; Tjoa, A Min; Weippl, Edgar
Web 2.0 has changed the technological landscape of the internet computing world today. The shift from traditional web which is also known as Web 1.0 is forced by the growing need for more efficient information sharing, collaboration, and business processes. The disclosure of personal/organisational information in Web 2.0 via social networks, digital contributions and data feeds has created new security and privacy challenges. Designing transparent, usable systems in support of personal privacy, security, and trust, requires advanced knowledge retrieval techniques that can support information sharing processes by applying appropriate policies. This paper proposes a Web 2.0 analysis methodology that provides reusable foundation components for information extraction, analysis and visualisation. These components can be used by the same method can be also used by individuals to make a self-test of their Web 2.0 contributions and find out what inferences will be derived from their web presence.